An analysis of antibiotic prescribing practices for enteric bacterial infections within FoodNet Canada sentinel sites. (20th January 2020) - Dougherty, Brendan; Finley, Rita; Marshall, Barbara; Dumoulin, Danielle; Pavletic, Amy; Dow, Joanne; Hluchy, Tara; Asplin, Rod; Stone, Jason
Abstract: Objectives: Understanding the current state of antibiotic treatment guidelines and prescribing practices for bacterial enteric infections is critical to inform antibiotic stewardship initiatives. This study aims to add to the current understanding through three objectives: (i) to identify and summarize published treatment guidelines for bacterial enteric infections; (ii) to describe observed antibiotic prescribing practices for bacterial enteric infections across three sentinel sites in Canada; and (iii) to assess concordance between observed antibiotic prescribing and treatment guidelines. Methods: An environmental scan of treatment guidelines for bacterial enteric infections was conducted and recommendations were collated. A descriptive analysis of cases of bacterial enteric illnesses captured in FoodNet Canada's sentinel site surveillance system between 2010 and 2018 was performed. Antibiotic-use data were self-reported by cases via an enhanced questionnaire. Results: Ten treatment guidelines were identified in the environmental scan. There was substantial variation between guidelines for both when to prescribe antibiotics and which antibiotics were recommended. Of the 5877 cases of laboratory-confirmed bacterial enteric illness in the three sites, 49% of cases reported having received an antibiotic prescription. Of particular significance was the finding that 21% of verotoxigenic Escherichia coli cases received a prescription. Of the 17 antibiotics recommended in the guidelines, 14 were used in practice. In addition to these, 18 other antibiotics not included in any of the guidelines reviewed were also prescribed. Conclusions: Our study suggests that a substantial proportion of enteric bacterial infections in Canada are prescribed antibiotics. These findings highlight the need to standardize treatment guidelines for enteric illnesses and could be used to inform future stewardship programme development.